The mediating role of charismatic leadership communication in a crisis: a Malaysian example - Jamal, Jamilah; Abu Bakar, Hassan (SAGE, 2015)
This study develops a model to advance research on public organization reputation by integrating crisis responsibility with charismatic leadership communication. Based on situational crisis communication theory, the model was tested using structural equation modeling with data obtained from a sample of 383 employees of public organizations in Malaysia. The mediation model indicated that the dynamic mechanism of charismatic leadership communication partially mediated the relationship between crisis responsibility and perceived organizational reputation during a crisis. These findings validated the proposed model and, in particular, confirmed empirically the central role of charismatic leadership communication processes in organization. This study provides insights into the role of charismatic leadership communication in the organizational reputation processes. The model established can serve as an instructive guide for both organization and corporate leaders in managing a crisis and reputation. A practical implication of the findings is that, during a crisis, a crisis leader should engage in charismatic leadership communication effectively to mitigate the crisis impact and strengthen organizational reputation. More important, the findings indicate that charismatic leadership communication contributed to organizational reputation explicitly brought charismatic leadership communication to the forefront of organizational reputation management.